Gendhing, King, and Events: The Creation of Gendhing Panembrama During Pakubuwana X - Daryanto, Joko; Rustopo, Rustopo; Sunarto, Bambang (Harmonia: Journal of Arts Research and Education, 2021)
Gendhing Panembrama was a creative and innovative product when Paku Buwana X reigned in the Negari Surakarta. Gendhing Panembrama emerged when the Dutch East Indies government imposed restrictions on political and economic activities in Karaton Surakarta. The restriction aimed to remove Paku Buwana X’s legitimacy from the political and economic side. Gendhing Panembrama became one of the symbols of Paku Buwana X’s resistance to the Dutch East Indies government policy. Resistance through the creation of Gendhing Panembrama resulted in the enforcement of the king of Surakarta’s sovereignty and legitimacy. This study aims to reveal the background of the Gendhing Panembrama creation and the events surrounding the Gendhing Panembrama creation. This study employed a historical approach and symbolic interpretation. From the study conducted, it was concluded that the creation of Gendhing Panembrama was a means for Paku Buwana X in maintaining his sovereignty and legitimacy. The intelligence of Paku Buwana X in managing the musical arts amid the political pressure of the Dutch East Indies government, in the end, could radiate his majesty, authority, and power and maintain the Javanese tradition of the Karaton Surakarta.